Multi-Party in Presidential System in Indonesia: What Does Democracy Mean? - Anita Indah Widiastuti (Universitas Negeri Semarang, 2020)
Article 1 paragraph (1) of the 1945 Constitution of the Republic of Indonesia has explained the form of the Indonesian state. The concept of trias politica assumes that state power consists of three kinds of power, namely legislative power/making laws or usually referred to as parliament (rule making of function), executive power/power to implement laws (rule application function), and power judiciary / power to adjudicate for violations of the law (rule adjudication function). The three powers in these state institutions are closely tied to each other and cannot be separated or there are checks and balances, which means that each branch of government divides its power distribution to other branches in order to limit its actions. This paper aims to analyze the Presidential system with the Multi-Party System in Indonesia in the context of democracy and the administration of state power.